THE ROLE OF WAQF ON HALAL INDUSTRY AND ISLAMIC ECONOMIC DEVELOPMENT IN INDONESIA: A SWOT ANALYSIS - Fakhri Sungit; Azwar Azwar (Tasharruf: Journal Economics and Business of Islam, 2023)
This study aims to analyze the strengths, weaknesses, opportunities, and threats as well as strategies for the role of waqf on halal industry and Islamic Economy development in Indonesia. This research is a qualitative descriptive study using literature study methods and SWOT analysis techniques. The results of the study show that the strengths of waqf in Indonesia lie in the existence of well-established waqf institutions, the existence of a Waqf Core Principle (WCP) as a guideline and the existence of a scheme that integrates social funds and commercial funds. However, Indonesia’s waqf also has several weaknesses, namely the not-yet optimal digitalization of user-friendly waqf collection, the lack of development of instruments that integrate waqf with merchant products, the large number of individual nazirs who are not registered and do not work full-time, and the distribution of most of the waqf funds to sectors that are relatively less productive. Meanwhile, the opportunities for waqf in Indonesia lie in the increasing diversity of multipayment services on various e-commerce sites, the high intention to donate from the Indonesian people, the increasing number of universities that specifically teach Sharia economics. However, the threats that must be faced are the lack of awareness regarding cash waqf, the lack of public literacy about waqf, and the dominant public perception of traditional waqf. Several strategic programs that can be carried out include: (1) increasing waqif and public awareness of waqf; (2) strengthening the waqf ecosystem; and (3) strengthening the institutional integration of zakat institutions.